Main bacteria of hospital infection after neurosurgery: A narrative review (Research, Society and Development, 2025)
Post-neurosurgical procedure infections, resulting from direct contact with bacteria within the surgical center, directly affect the patient's good prognosis, leading to complications that can lead to admission to the intensive care unit (ICU). According to a survey of data from the World Health Organization (WHO), in Brazil alone, surgical site infections (SSI) are responsible for around 15% of all infections related to healthcare, increasing the average length of stay in the ICU by 60%. The Central Nervous System (CNS) controls the body's functions, guiding almost everything through signals in networks of neurons and releasing substances at the tips of cells. The nervous tissue feels everything from the outside and inside, reacting by sending rapid and constant nervous warnings. In summary, central nervous system infections continue to be a significant burden on healthcare systems around the world. However, advances made in understanding its pathophysiology in the last 20 years surpass anything that has been done before.